Forging the Middle Ground : Engaging Non-state Justice in Indonesia - World Bank (World Bank, Washington, DC, 2018)
The objective of this research was to document the workings of non-state justice at the village level, with a particular focus on social inclusion and the perspectives of the marginalized. The paper also sought to understand the dynamics of change and how to translate them into a framework that embraces the strengths and addresses some of the shortcomings of non-state justice. It draws on 34 ethnographic case studies collected from five provinces in Indonesia over an eighteen month period and quantitative survey data from the 2006 Governance and Decentralization Survey. This paper will help to expand understanding of the complex and varied processes of non-state justice and thus help policy makers find new ways of building an effective legal and judicial system accessible by all Indonesians. This paper proposes a framework for forging a meaningful middle ground between the current practices of non-state justice and the formal justice system. This approach seeks to marry the social accessibility, authority and legitimacy of informal processes with accountability to the community and the state. This middle ground attempts to accommodate different socio-cultural contexts, customs and habits but at the same time introduces common principles to protect the marginalized.